Artemin Is Upregulated by TrkB Agonist and Protects the Immature Retina Against Hypoxic-Ischemic Injury by Suppressing Neuroinflammation and Astrogliosis - Huang, Hsiu-Mei; Huang, Chao-Ching; Poon, Linda Yi-Chieh; Chang, Ying-Chao (Frontiers in Molecular Neuroscience, 2021)
Hypoxic-ischemia (HI) is a major cause of acquired visual impairment in children from developed countries. Previous studies have shown that systemic administration of 7,8-dihydroxyavone (DHF), a selective tropomyosin receptor kinase B (TrkB) agonist, provides long-term neuroprotection against HI injury in an immature retina. However, the target genes and the mechanisms of the neuroprotective effects of TrkB signaling are not known. In the present study, we induced an HI retinal injury through unilateral common carotid artery ligation followed by 8% oxygen for 2 h in P7 rat pups. DHF was administered intraperitoneally 2 h before and 18 h after the HI injury. A polymerase chain reaction (PCR) array was used to identify the target genes upregulated after the DHF treatment, which was then confirmed with quantitative real-time reverse transcriptase PCR and a western blot. Effects of the downstream mediator of DHF were assessed using an intravitreal injection of neutralizing antibody 4 h after DHF administration (24 h after HI). Meanwhile, the target protein was injected into the vitreous 24 h after HI to validate its protective effect when exogenously supplemented. We found that systemic DHF treatment after HI significantly increased the expression of the artemin (ARTN) gene and protein at P8 and P10, respectively. The neuroprotective effects of DHF were inhibited after the ARTN protein blockade, with an increase in neuroinflammation and astrogliosis. ARTN treatment showed long-term protection against HI injury at both the histopathological and functional levels. The neuroprotective effects of ARTN were related to a decrease in microglial activation at P17 and attenuation of astrogliosis at P29. ARTN enhances phosphorylation of RET, ERK, and JNK, but not AKT or p38 in the immature retina. Altogether, these results suggest that the neuroprotective effect of a TrkB agonist is partially exerted through a mechanism that involves ARTN because the protective effect is ameliorated by ARTN sequestration. ARTN treatment after HI injury protects the immature retina by attenuating late neuroinflammation and astrogliosis in the immature retina relating to the ARTN/RET/JNK/ERK signaling pathway. ARTN may be a strategy by which to provide long-term protection in the immature retina against HI injury.